Calculation of waveguide modes in linear chains of metallic nanorods - C. Tserkezis; N. Stefanou (Journal of the Optical Society of America B, 2012)
We report on the calculation of the fundamental plasmon waveguide modes in linear periodic chains of finite silver nanorods, aligned perpendicular to the chain. The results of rigorous full-electrodynamic calculations by the layer-multiple-scattering method are discussed in conjunction with the results of the widely used coupled-dipole model and a critical evaluation of the latter is provided. More specifically, it is shown that both diameter and height of the nanorods must be much smaller than the interparticle distance; otherwise, for relatively long nanorods close to each other, the coupled-dipole model can fail completely to predict the waveguide dispersion diagram. Moreover, the model systematically underestimates the effect of dissipative losses and cannot describe the effect of a supporting substrate, which is always present in realistic cases and induces considerable changes in the waveguide dispersion diagram.